(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In this study, we have two independent variables: Total Quality Management (TQM), Technological Processes, and dependent variable: Organizational Assessment Management (OAM). Our findings demonstrate that these two independent variables, working together, significantly influence (OAM). Or a known quantity of words or paragraphs, in measuring the mature role in (TQM) and technological processes, and identifying the highest state of performance movement on the impact of organizational evaluation management. It relied on the most suitable journals to update everything that is most appropriate for performance and to eliminate any gap, whatever its nature, that might undermine our work. Two hundred employees from Al-Qadisiyah University / Iraq were surveyed. (200) responses were deemed inconclusive in their original form. (4) were missing, Net (196). The Likert (7) was used in the questionnaire. The )SPSS( statistical software was used. The hypotheses (2) were positive.